Performance of NDVI Index on HPC Resources - Saribekyan, Albert G. (Mathematical Problems of Computer Science, 2021)
Geographic information systems (GIS) [1] are crucial to enable the gathering, analysis, presentation and distribution of spatial and non-spatial data. In some specific GIS applications, such as time-critical simulations or data mining, we need to deal with massive amount of geospatial data storage, retrieval, and processing. The main aim of this article is to analyze and benchmark the performance of Normalized Difference Vegetation Index (NDVI) [2] of satellite images (16 GB [3]) using highperformance computational (HPC) resources, as the developers need to solve the problem of both data and task distribution among serial or parallel environments. The geographical resources analysis support system (GRASS) [4] is used as the main instrument for the study.